Efektivitas Pelaksanaan Bimbingan Kelompok dengan Pendekatan Konseling Realitas dalam Mengembangkan Penyesuaian Diri Siswa di Lingkungan Sekolah pada Siswa Kelas X SMAN 1 Sungai Tarab - Mariah, Kiki; S, Neviyarni; Jamna, Jamaris (Universitas Negeri Padang, 2016)
Self Adjustmentin school environment is a process that covers mental responses and behavior change in which the students struggle for managing their needs, tension, conflicts and frustration so that they could harmonize their needs and the school’s demands. One of the approaches done to develop the students’ self adjustment was reality therapy. This research was aimed at revealing: the average score of the students’ self adjustment in school environment before and after reality therapy was applied; and the effectiveness of group counseling by using reality therapy approach in developing the students’ self adjustment in school environment.This research applied quantitative method. This was a pre-experimental research which used the one group pre-test post-test design. The subject of the research was chosen by using non-random sampling technique and purposive sampling method. The subject consisted of twelve students who were categorized into maladjustment and well adjusted. This research was conducted at SMAN 1 Sungai Tarab for six meetings. The instrument of the research was self adjustment scale of Likert scale model. The data gathered were analyzed by using Wilcoxon Signed Ranks Test of statistic non-parametric technique assisted with SPSS version 20.00.The research findings revealed that, in general, group counseling by using reality therapy approach was effective in developing the students’ self adjustment in school environment. Meanwhile, in particular, there was a difference between self adjustment score of the students before and after group counseling by using reality therapy approach was applied. Based on the research findings, it was conluded that the students’ self adjustment in school environment could be developed through group counseling by using reality therapy approach.